2018
DOI: 10.1016/j.bmc.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Facile construction of fused benzimidazole-isoquinolinones that induce cell-cycle arrest and apoptosis in colorectal cancer cells

Abstract: Colorectal cancer (CRC) is one of the most frequent, malignant gastrointestinal tumors, and strategies and effectiveness of current therapy are limited. A series of benzimidazole-isoquinolinone derivatives (BIDs) was synthesized and screened to identify novel scaffolds for CRC. Of the compounds evaluated, 7g exhibited the most promising anti-cancer properties. Employing two CRC cell lines, SW620 and HT29, 7g was found to suppress growth and proliferation of the cell lines at a concentration of ∼20 µM. Treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Cell apoptosis assays were based on the previous description [ 16 ]. Flow cytometry was performed with an annexin V-FITC apoptosis detection kit (Beyotime, C1063, Shanghai, China) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Cell apoptosis assays were based on the previous description [ 16 ]. Flow cytometry was performed with an annexin V-FITC apoptosis detection kit (Beyotime, C1063, Shanghai, China) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…In the previous study, we found that compound-7g was an effective inhibitor against colorectal cancer cells through impairing PI3K/AKT/mTOR signaling pathway [14]. The structure of compound-7g is shown in Figure 1A.…”
Section: Resultsmentioning
confidence: 99%
“…While in case of MIL treated parasite lower values were obtained (sub-G0/G1: 10.19%, S: 1.06%, and G2/M: 0.18%). These findings suggest that C1 arrests parasites in sub-G0/G1 phase and induces cell death resembling apoptosis [59][60][61][62][63] . We could also observe that approximately 8.69% treated parasite population was annexinV-positive and PI-negative (Fig.…”
Section: C1 Induces Sub-g0/g1 Phase Cell-division Arrest and Phosphatmentioning
confidence: 87%